2002
DOI: 10.1016/s1010-7940(02)00448-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of morbidity and in-hospital mortality in obese patients undergoing coronary artery bypass surgery

Abstract: Obese patients are not associated with an increased risk of in-hospital mortality following coronary artery bypass surgery. In contrast, there is a significant increased risk of morbidities and post-operative length of stay in obese patients compared to non-obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
95
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 18 publications
8
95
1
Order By: Relevance
“…Similar to our findings, Kuduvalli et al [13] surveyed 4,713 patients who underwent isolated CABG and confirmed that obese patients were more likely to have prolonged mechanical ventilation. However, they found no association between BMI and mortality, stroke, MI, bleeding, or re-exploration, but they did find a significant association between obesity and sternal infection, which was inconsistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to our findings, Kuduvalli et al [13] surveyed 4,713 patients who underwent isolated CABG and confirmed that obese patients were more likely to have prolonged mechanical ventilation. However, they found no association between BMI and mortality, stroke, MI, bleeding, or re-exploration, but they did find a significant association between obesity and sternal infection, which was inconsistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Jenkins and Moxham [29] also reported that obesity has adverse effects on pulmonary function through increased functional residual capacity, decreased vital capacity, and maximum voluntary ventilation; our findings are in consistence with previous reports. [11,13] Likewise, other authors have reported greater respiratory problems and subsequent longer mechanical ventilation times after CABG among underweight patients. [4,9] Based on our findings, it seems that the association between post-CABG pulmonary complications and preoperative BMI also follows a U-shaped pattern, with both very high and very low ranges.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Preoperative factors associated with increased incidence of SV infection include increased age, 10,11 female sex, 9,12-14 increased body mass index, 9,10,13,[14][15][16] and comorbidities such as DM, 9,[11][12][13]17 PVD, [11][12][13] low preoperative hemoglobin levels, 14 congestive heart failure, and chronic renal failure, whereas the peroperative factors include duration of surgery, open technique of harvesting, 1,18-21 harvesting from the leg with deep vein thrombosis, inappropriate use of electrocautery, and IABP use, and these factors are modifiable.…”
Section: Risk Factors Associated With Gsvhsimentioning
confidence: 99%